Green Technology Innovation of Energy Internet Enterprises: Study on Influencing Factors under Dual Carbon Goals - Yichang Zhang; Sha He; Min Pang; Qiong Li (Energies, 2023)
In order to help Energy Internet (EI) enterprises develop sustainably, promote the transformation and upgrading of energy systems and achieve the goal of carbon peaking and carbon neutrality, a study on the influencing factors of green technology innovation (GTI) in EI enterprises was conducted using the Decision-making Trial and Evaluation Laboratory-Adversarial Interpretive Structure Modeling Method (DEMATEL-AISM). Through a literature review and field research, the DEMATEL-AISM-based model of the GTI influencing factors of EI enterprises was constructed on the basis of summarizing the system of GTI influencing factors of EI enterprises, visualizing the interrelationship and hierarchical structure among GTI influencing factors of EI enterprises and finally proposing relevant countermeasures and suggestions. This study shows that the proximity-level factors such as R&D investment and external cooperation directly affect the GTI of EI enterprises; the essential-level factors such as environmental regulation and development strategy are the root causes of the GTI of EI enterprises. The transition-level factors such as market competition and business model are the key nodes of the GTI of EI enterprises, and the above factors should be focused on.